2014
DOI: 10.3233/ves-140513
|View full text |Cite
|
Sign up to set email alerts
|

Acute alcohol intoxication impairs segmental body alignment in upright standing

Abstract: Balance control when standing upright is a complex process requiring input from several partly independent mechanisms such as coordination, feedback and feedforward control, and adaptation. Acute alcohol intoxication from ethanol is recognized as a major contributor to accidental falls requiring medical care. This study aimed to investigate if intoxication at 0.06 and 0.10% blood alcohol concentration affected body alignment. Mean angular positions of the head, shoulder, hip, and knee were measured with 3D-mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(64 reference statements)
1
3
0
Order By: Relevance
“…[52][53][54][55] Immediately postuse, individuals in both groups demonstrated a modest performance decrement on a moderately challenging balance task (quiet standing with no vision), and these short-term changes appeared to recover within an hour. The degree of balance impairment (approximately 11% increase in sway with eyes closed from preuse to postuse) found is consistent with prior balance effects of moderate alcohol (eg, 0.05%-0.10% blood alcohol concentration 56 ) and lower-potency THC administration in regular users. 57 These results provide evidence that balance impairment could be a useful marker of recent cannabis use, even in regular users of highly potent products who show tolerance to shortterm cannabis use in other domains.…”
Section: Discussionsupporting
confidence: 78%
“…[52][53][54][55] Immediately postuse, individuals in both groups demonstrated a modest performance decrement on a moderately challenging balance task (quiet standing with no vision), and these short-term changes appeared to recover within an hour. The degree of balance impairment (approximately 11% increase in sway with eyes closed from preuse to postuse) found is consistent with prior balance effects of moderate alcohol (eg, 0.05%-0.10% blood alcohol concentration 56 ) and lower-potency THC administration in regular users. 57 These results provide evidence that balance impairment could be a useful marker of recent cannabis use, even in regular users of highly potent products who show tolerance to shortterm cannabis use in other domains.…”
Section: Discussionsupporting
confidence: 78%
“…The goal of this task was to assess finger tapping speed, a validated measure of general motor function that has been used to assess fine motor control and simple motor speed after intoxication (42)(43)(44)(45)(46).…”
Section: Index Finger Tappingmentioning
confidence: 99%
“…It is hypothesized that the MC and head movement can be used to predict intoxication. As Hafström, Patel, et al [16] discovered, an increased BAC level significantly affected head position due to decreased visual input. The head is more anterior as visual input is decreased.…”
Section: Introductionmentioning
confidence: 98%
“…There are no known methods of detecting whether an MC rider is intoxicated while riding the MC. Hafström, Patel, et al [16] showed that poor visual input caused by intoxication and disrupted vestibular information cause unreliable posture feedback. The head loses its vertical position and deviates to the left.…”
Section: Introductionmentioning
confidence: 99%